-18-6g=6+18g

Simple and best practice solution for -18-6g=6+18g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18-6g=6+18g equation:


Simplifying
-18 + -6g = 6 + 18g

Solving
-18 + -6g = 6 + 18g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-18g' to each side of the equation.
-18 + -6g + -18g = 6 + 18g + -18g

Combine like terms: -6g + -18g = -24g
-18 + -24g = 6 + 18g + -18g

Combine like terms: 18g + -18g = 0
-18 + -24g = 6 + 0
-18 + -24g = 6

Add '18' to each side of the equation.
-18 + 18 + -24g = 6 + 18

Combine like terms: -18 + 18 = 0
0 + -24g = 6 + 18
-24g = 6 + 18

Combine like terms: 6 + 18 = 24
-24g = 24

Divide each side by '-24'.
g = -1

Simplifying
g = -1

See similar equations:

| 9xy-9=3x+2 | | X^2+17=66 | | 200m-100m+48000=50500-150m | | 5x+11=29-3x | | 7a-10=11 | | -7(x-15.6)=9 | | 16=2n+10 | | (3x-3)=(2x+13) | | -6(-3y+3)-6y=2(y-9)-5 | | 2=2b-16 | | 2=3(x-1)+4-2x | | -2=-(t-8) | | 15x^4-35x^2=0 | | 7a(a+5)-(a+5)=0 | | -7x+25+9x+25=-4 | | 10e+1h+0.125x=100 | | 10=2w+6 | | z^3-5z^2+2z+10=0 | | 5*n+5j=z | | 2+7n=-2+7n | | 2x+11=900 | | 3x(x-5)=6x^2-16 | | 7a-2+3=8 | | 5n+5j=z | | 3(b-2)+5=9 | | 4a+3b=6b-9b | | 17+2p=21+2p | | (5x^2+8x)(20x^2-11x-4)=0 | | (3z+6z)+7=29-4 | | 5x-3x(2-8)=112 | | -5-8y=-77 | | -6(r+8)=-8(r-3) |

Equations solver categories